Experimental and Numerical Studies of the Film Cooling Effectiveness Downstream of a Curved Diffusion Film Cooling Hole. (9th May 2022) - Yang, Fan; Taslim, Mohammad E.
Abstract : Film cooling technology is a commonly used method for thermal protection of gas turbines' hot sections. A new, shaped, film cooling hole is proposed in this study. The geometry is made of a straight-through cylindrical feed hole at an inclination angle of 30° followed by an expansion section. The expansion section is created by the rotation of the same circular hole on the inclination plane about an axis normal to that plane which passes through the center of the feed hole exit area. This shape was designed to decrease the deteriorating effects of kidney vortices by proper distribution of the coolant flow emerging from the hole exit area. Cases with four rotation angles (7°, 14°, 17.5°, and 21°) were studied both experimentally and numerically and for the blowing ratios of 0.5, 1, and 2.0. For comparisons, the commonly used 7°-7°-7° diffusion hole geometry was also tested under otherwise identical conditions. For data collection, the pressure-sensitive paint (PSP) technique was used to measure the film cooling effectiveness. Streamwise- and spanwise-averaged film effectiveness results were obtained to compare the performance of different geometries. The main conclusions were that the case of 21° rotation angle produced the highest film effectiveness and outperformed the 7°-7°-7° diffusion hole geometry.